Inclusão de crianças autistas no processo de leitura - SILVA, Claudilene dos Santos (2018)
It presents the importance of reading in the socialization of children with Autism Spectrum Disorder (ASD) as a therapy to optimize their learning the interpersonal relationship of the individual, encouraging their autonomy and social interaction through bibliotherapy, highlighting the role of the librarian in this context as a transformation agent in the mediation of reading. The methodology was carried out in two stages: bibliographic research in books and scientific articles and field research, through the observation through data collection with application of questionnaires directed to the multidisciplinary team of the Center for Reference in Educational Inclusion Gabriel Lima Mendes (CRIE) where 21 children with ASD from the municipal education network attend. Based on this research, it is concluded that the lack of reading incentive projects for autistic children highlights the lack of a librarian in this institution to select specific literatures tailored to the needs of these individuals in order to help them achieve good educational results, applying the method of reading that he deems most effective to improve his cognitive and social skills.